KEPEMIMPINAN KEPALA SEKOLAH DAN STRATEGI GURU DALAM PENGUATAN TOLERANSI BERAGAMA DI SEKOLAH SMA HANG TUAH - Andi, Ahmad al muhajir; Syamsul, Syamsul; Alwan suban; Ermi Sola (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the role of the principal and teacher strategies in strengthening religious tolerance at Hang Tuah Senior High School in Makassar. The focus of the study is directed at understanding how the principal's leadership contributes to creating an inclusive school environment, as well as how teachers implement learning strategies and role models in instilling values of tolerance in students. The urgency of this research is based on the school's religious diversity, yet it lacks a structured program to strengthen tolerance.The research method used was qualitative research with a descriptive approach. Data were collected through observation, in-depth interviews, and documentation involving the principal, teachers, and students. Data validity was tested using source and method triangulation techniques. Data were analyzed using the stages of data reduction, data presentation, and conclusion drawing.The research results show that the principal acts as an educator, motivator, innovator, and role model in strengthening religious tolerance. The principal also promotes a culture of mutual respect, fosters dialogue, and provides guidance to teachers on integrating tolerance into school activities. Meanwhile, teachers implement values-based learning strategies, model behavior, promote inclusive religious programs, and develop communication that prioritizes mutual respect both inside and outside the classroom. The combination of the principal's role and teacher strategies significantly influences the development of tolerance in students.